Perceptions, Knowledge, and Attitudes about Human Trafficking Questionnaire: Extending Its Utility with Social Work Students. (30th October 2021) - Welch-Brewer, Chiquitia; Nsonwu, Maura; Busch-Armendariz, Noël; Heffron, Laurie Cook
Abstract: This study, a two-site, cross-sectional survey of university students ( n = 321 at site 1; n = 201 at site 2), extends the development and utility of the Perceptions, Knowledge, and Attitudes about Human Trafficking Questionnaire by generating factor-based scales and scores to represent values for its three factors (Self-Appraisal of Knowledge/Skills, Worldview of Human Trafficking, and Help-Seeking Behavior/Personal Beliefs) in order to examine their relationship to background criterion variables and assess differences between social work and non–social work students and between subgroups of social work students. Across both samples, the background variables of human trafficking training and professional responsibilities related to addressing human trafficking were predictive of self-appraisal of knowledge/skills. Additionally, social work students had higher scores than non–social work students on the worldview of human trafficking and help-seeking behavior/personal beliefs factor-based scales, suggesting that social work students perceived human trafficking to be more of a social problem and held fewer misperceptions of the help-seeking behavior of and a greater willingness to provide social services to persons who are trafficked than non–social work students. Implications for social work education, practice, and research are presented.